Brain ureido degenerative protein modifications are associated with neuroinflammation and proteinopathy in Alzheimer’s disease with cerebrovascular disease - Gallart-Palau, Xavier; Serra, Aida; Lee, Benjamin Sian Teck; Guo, Xue; Sze, Siu Kwan (Journal of neuroinflammation, 2017)
Brain degenerative protein modifications (DPMs) are associated with the apparition and progression of dementia, and at the same time, Alzheimer's disease with cerebrovascular disease (AD + CVD) is the most prevalent form of dementia in the elder population. Thus, understanding the role(s) of brain DPMs in this dementia subtype may provide novel insight on the disease pathogenesis and may aid on the development of novel diagnostic and therapeutic tools. Two essential DPMs known to promote inflammation in several human diseases are the ureido DPMs (uDPMs) arginine citrullination and lysine carbamylation, although they have distinct enzymatic and non-enzymatic origins, respectively. Nevertheless, the implication of uDPMs in the neuropathology of dementia remains poorly understood. In this study, we use the state-of-the-art, ultracentrifugation-electrostatic repulsion hydrophilic interaction chromatography (UC-ERLIC)-coupled mass spectrometry technology to undertake a comparative characterization of uDPMs in the soluble and particulate postmortem brain fractions of subjects diagnosed with AD + CVD and age-matched controls. An increase in the formation of uDPMs was observed in all the profiled AD + CVD brains. Citrulline-containing proteins were found more abundant in the soluble fraction of AD + CVD whereas homocitrulline-containing proteins were preferentially abundant in the particulate fraction of AD + CVD brains. Several dementia-specific citrulline residues were also identified in soluble proteins previously categorized as pro-immunogenic, which include the receptor P2X7, alpha-internexin, GFAP, CNP, MBP, and histones. Similarly, diverse dementia-specific homocitrulline residues were also observed in the particulate fractions of AD + CVD in proteins that have been vastly implicated in neuropathology. Intriguingly, we also found that the amino acids immediately flanking arginine residues may specifically influence the increase in protein citrullination. Taken together, these results indicate that uDPMs widely contribute to the pathophysiology of AD + CVD by promoting neuroinflammation and proteinopathy. Furthermore, the obtained results could help to identify disease-associated proteins that can act as potential targets for therapeutic intervention or as novel biomarkers of specific neuropathology.